In vivo anti-hyperuricemic activity of sesquiterpene lactones from Lychnophora species. - Bernardes, Ana Catharina Fernandes Pereira Ferreira (2020)
Hyperuricemia is the main cause of gout, an inflammation induced by uric acid deposition in joints. Drugs available present side effects, so there is a need for new treatment alternatives. Lychnophora species are used in folk medicine to treat inflammation, rheumatism and muscle pain. Goyazensolide (10 mg/kg), eremantholide C (25 mg/kg) and lychnopholide (25 mg/kg), sesquiterpene lactones isolated from Lychnophora species were previously studied and showed anti-hyperuricemic effects in mice. However, the mechanisms of this effect were not elucidated. The methodology of this study consisted in treatment of hyperuricemic-induced rats, and comparison between control groups, clinically used anti-hyperuricemic drugs and sesquiterpene lactones. Urine and blood were collected for uric acid quantification. Xanthine oxidase inhibition was measured in liver homogenates. Results showed that all evaluated sesquiterpene lactones presented anti-hyperuricemic activity at the doses of 5 and 10 mg/kg and can act through one or both mechanisms, depending on the dose administrated. Goyazensolide and lychnopholide at dose of 5 mg/kg showed important uricosuric effect. Goyazensolide and lychnopholide at dose of 10 mg/kg, and eremantholide C (5 and 10 mg/kg) presented notable inhibition of hepatic xanthine oxidase activity and uricosuric effect. Thus, these sesquiterpene lactones are promising hypouricemic agent to treat hyperuricemia and gout.